Studies on Physico-chemical Characteristics of Pomegranate Cultivars Grown Under Arid Conditions - Mali, P C; Prasad, R N (Annals of Arid Zone, 2016)
Different pomegranate cultivars, grown successfully under arid conditions, were .evaluated with respect to their physico-chemical characteristics. IL revealed that inter-varietal differences were highly significant for most of the physical parameters such as weight of fruits (g) and contents (%) of juice. aril, rind, and seed. The fruit cracking was quite high in cv. Jodhpur Red, whereas it was least in cv. Â Jalore seedless. A high juice content (fruit weight basis), ranging from 40.8 to 52.7%, was recorded in various cultivars. In general. all the cultivars were found to contain high fraction of reducing sugar as a part of total sugar. The acidity in terms of citric acid was quite high (1.78%) in cv. Basin seedless, and least (0.189%) in cv. Jodhpur Red.